Assessing the combined toxicity effects of three neonicotinoid pesticide mixtures on human neuroblastoma SK-N-SH and lepidopteran Sf-9 cells. (November 2020) - Cheng, Lin; Lu, Yangyang; Zhao, Zhihui; Hoogenboom, Ron L.A.P.; Zhang, Qicai; Liu, Xing; Song, Wei; Guan, Shuhui; Song, Weiguo; Rao, Qinxiong
Abstract: Neonicotinoid insecticides have been widely used in plant protection against pests worldwide. Generally, more than one neonicotinoids are detected in plants and foods, and such mixtures may show combined toxicity and increase the risk for both insects and higher organisms. In this study, the combined toxicity of imidacloprid (IM), acetamiprid (AC) and thiamethoxam (TH) was investigated using human neuroblastoma cell line (SK-N-SH) and lepidopteran cell line (Sf-9). Results showed that binary and ternary mixtures could enhance the inhibition of growth of both SK-N-SH and Sf-9 cells at low doses. In SK-N-SH cells, based on CompuSyn software analysis, all the mixtures of IM+AC, IM+TH, AC+TH and IM+AC+TH showed synergistic effects at concentrations < 50 mg/L, but IM+AC, IM+TH showed antagonistic effects at higher concentrations. For Sf-9 cells, all mixtures revealed synergistic effects at low concentrations (< 0.1 mg/L) except IM+AC, showing antagonism at higher concentrations (> 0.5 mg/L). The toxicity thresholds of mixtures denoted by BMDL10 values were all lower than those for single pesticides and the combined BMDL10 value of AC+TH was the lowest one. It is concluded that the co-occurrence of several neonicotinoid insecticides may enhance their toxicity and aggravate the health risk for both insects and human. Graphical abstract: Image 1 Highlights: Thiamethoxam had the highest toxic potential both on Sf-9 and SK-N-SH cells. Synergy effects observed from combined treatment at low concentration. The benchmark dose lower bound of acetamiprid plus thiamethoxam was the lowest one.